Glycolytic reprogramming in macrophages and MSCs during inflammation - Li, Xueping; Shen, Huaishuang; Zhang, Mao; Teissier, Victoria; Huang, Ejun Elijah; Gao, Qi; Tsubosaka, Masanori; Toya, Masakazu; Kushioka, Junichi; Maduka, Chima V.; Contag, Christopher H.; Chow, Simon Kwoon-Ho; et al. (Frontiers in Immunology, 2023)
Background: Dysregulated inflammation is associated with many skeletal diseases and disorders, such as osteolysis, non-union of fractures, osteonecrosis, osteoarthritis and orthopaedic infections. We previously showed that continuous infusion of lipopolysaccharide (LPS) contaminated polyethylene particles (cPE) caused prolonged inflammation and impaired bone formation. However, the metabolic and bioenergetic processes associated with inflammation of bone are unknown. Mitochondria are highly dynamic organelles that modulate cell metabolism and orchestrate the inflammatory responses that involve both resident and recruited cells. Glycolytic reprogramming, the shift from oxidative phosphorylation (OXPHOS) to glycolysis causes inappropriate cell activation and function, resulting in dysfunctional cellular metabolism. We hypothesized that impaired immunoregulation and bone regeneration from inflammatory states are associated with glycolytic reprogramming and mitochondrial dysfunction in macrophages (Mφ) and mesenchymal stromal cells (MSCs).